Description of Knowledge, School Snack Consumption Behavior and Nutritional Status of Elementary School Latukan, Lamongan Regency - Farikha Fidinilla Trias Prinanta; Annas Buanasita; Taufiqurrahman; Nuning Marina Pengge (Politeknik Kesehatan Kemenkes Surabaya, 2024)
The growth and development of elementary school-aged children require adequate nutrition. A preliminary study conducted on 10 students of Latukan Elementary School revealed that 20% of them were overweight, 60% had good nutritional status, and 20% were underweight. However, this preliminary study failed to provide a comprehensive understanding of the knowledge, snack consumption behavior, and nutritional status of students at Latukan Public Elementary School in Lamongan Regency. To address this gap, a descriptive study was conducted to determine the knowledge, consumption behavior of school snacks, and nutritional status of elementary school students in Latukan, Lamongan Regency. The study population comprised 66 students, with a sample size of 40 students selected through proportional random sampling. Data were collected through interviews using questionnaires and food frequency questionnaires. The findings revealed that 55% of the students had good knowledge, 55% exhibited moderate behavior, 57.5% consumed school snacks frequently, and 62.5% had good nutritional status. Moreover, 22.5% of the students were categorized as having more nutritional needs. This research aims to raise awareness among the community regarding the importance of nutritional knowledge and healthy snack consumption habits among school-aged children.